Methods for improving solvent properties - Hernberg, Tero (2019)
In hydrometallurgical processes, the separation of nickel and cobalt is challenging. Cyanex272 dialkyl phosphinic acid is generally used to separatet hese elements. The most eﬀective separation requires that the reaction mixture be as pure as possible from various interferences such as carboxylic acids. This thesis investigates various possibilities for removing carboxylic acids from the extraction mixture. Possibility of utilizing diﬀerent pH isotherms and diﬀerent water solubilities of carboxylic acids and Cyanex 272 for separation was investigated. Normal phase chromatography was attempted with one minute fractioning and ﬁnally molecular catcher was tested. Separation of extractants in these experiments, with these parameters failed.Possibility of utilizing diﬀerent pH isotherms and diﬀerent water solubilities of carboxylic acids and Cyanex 272 for separation was investigated. Normal phasechromatographywasattemptedwithoneminutefractioningandﬁnally molecular catcher was tested. Separation of extractants in these experiments, with these parameters failed